Knee and ankle joint torque-angle relationships of multi-joint leg extension - Hahn, D.; Olvermann, M.; Richtberg, J.; Seiberl, W.; Schwirtz, A. (Journal of Biomechanics, 2011)
The force-length-relation (F-l-r) is an important property of skeletal muscle to characterise its function, whereas for in vivo human muscles, torque-angle relationships (T-a-r) represent the maximum muscular capacity as a function of joint angle. However, since in vivo force/torque-length data is only available for rotational single-joint movements the purpose of the present study was to identify torque-angle-relationships for multi-joint leg extension. Therefore, inverse dynamics served for calculation of ankle and knee joint torques of 18 male subjects when performing maximum voluntary isometric contractions in a seated leg press. Measurements in increments of 10° knee angle from 30° to 100° knee flexion resulted in eight discrete angle configurations of hip, knee and ankle joints. For the knee joint we found an ascending-descending T-a-r with a maximum torque of 289.5°±43.3 N m, which closely matches literature data from rotational knee extension. In comparison to literature we observed a shift of optimum knee angle towards knee extension. In contrast, the T-a-r of the ankle joint vastly differed from relationships obtained for isolated plantar flexion. For the ankle T-a-r derived from multi-joint leg extension subjects operated over different sections of the force-length curve, but the ankle T-a-r derived from isolated joint efforts was over the ascending limb for all subjects. Moreover, mean maximum torque of 234.7±56.6 N m exceeded maximal strength of isolated plantar flexion (185.7±27.8 N m). From these findings we conclude that muscle function between isolated and more physiological multi-joint tasks differs. This should be considered for ergonomic and sports optimisation as well as for modelling and simulation of human movement.